SIAPIK: Solusi mudah digitalisasi laporan keuangan bagi UMKM dI Desa Sukosari-Kabupaten Magelang - Panjawa, Jihad Lukis; Prakoso, Jalu Aji; Giovanni, Axel (Penamas: Journal of Community Service, 2022)
The purpose of implementing community service (PkM) is to increase knowledge of preparing financial reports using the SIAPIK application in the orderly preparation of financial reports for Small, Micro and Medium Enterprises (MSMEs). The steps of PkM activities are through lectures in explaining in theory the importance of financial reports and demonstrating / practising in preparing financial reports using smart phones through the SIAPIK application issued by Bank Indonesia. PkM activities were carried out by socialising and assisting in recording financial transactions through the use of the SIAPIK application to MSME actors in Sukosari Village, Bandongan District, Magelang Regency. The results of the activity include business actors dominated by women in the activity of preparing financial reports digitally using the SIAPIK application rather than men. Participants who participated in the activity had an education level of elementary / equivalent to high school / vocational / equivalent. The businesses carried out by the participants are all individuals with businesses run in the form of trade and service businesses. Through socialisation and training activities in preparing financial reports, business actors are able to apply them to their respective business activities properly.